Cormorants have negligible seascape-scale impacts on benthic vegetation communities - Karine Gagnon; Elina A. Virtanen; Pekka Rusanen; Marco Nurmi; Markku Viitasalo; Veijo Jormalainen (Inter-Research, 2022)
Cormorant populations in the Baltic Sea have rapidly expanded since the 1990s, raising concerns about their ecosystem impacts. Nutrient runoff from colonies, as well as cormorant predation on fish, can affect surrounding producer communities. Past studies have found cormorant impacts on producers in the immediate vicinity of colonies, but the importance of cormorants over a larger spatial scale is unknown, especially compared to other environmental variables. We used an extensive underwater vegetation inventory dataset (~18 000 data points along the Finnish coast) to determine the effects of cormorant colonies on macroalgae and plants. We compared community structure and species abundance/occurrence in near-colony (<5 km from a colony) and control (>10 km from a colony) points, and determined the importance of cormorant influence (using an index incorporating colony size and distance from the colony) in near-colony sites. We found no significant differences in community structure between near-colony and control points in most habitats, and adding cormorant index only infinitesimally improved statistical models after incorporating other environmental factors. However, the abundance of several species did differ, in particular the foundation species bladderwrack (Fucus vesiculosus) and eelgrass (Zostera marina) were either less likely to occur in near-colony points or negatively correlated with cormorant index, possibly due to the effects of nutrient enrichment from colonies. Our findings confirm that cormorants can have effects on some producer species, but highlight that these effects are negligible when taking into account the scale and magnitude of other bottom up and top-down processes occurring in the Baltic Sea.